2020
DOI: 10.3390/cryst10050405
|View full text |Cite
|
Sign up to set email alerts
|

Unseeded Crystal Growth of (100)-Oriented Grain-Boundary-Free Si Thin-Film by a Single Scan of the CW-Laser Lateral Crystallization of a-Si on Insulator

Abstract: Laser crystallization of a-Si film on insulating substrate is a promising technology to fabricate three-dimensional integrations (3D ICs), flat panel displays (FPDs), or flexible electronics, because the crystallization can be performed on room temperature substrate to avoid damage to the underlying devices or supporting plane. Orientation-controlled grain-boundary-free films are required to improve the uniformity in electrical characteristics of field-effect-transistors (FETs)fabricated in those films. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…[ 118 ] Moreover, it has recently been demonstrated that a silica cap is necessary to be able to obtain grain‐boundary‐free lateral crystallization of a‐Si thin films on glass substrates, using a fast CW laser scan. [ 119 ] Therefore, laser thermal processing of patterned and glass‐encapsulated Si waveguides could result in low optical losses similar to those achieved in SOI platforms and in the Si core glass‐clad fibers, but with the prospect of allowing for photonic integration within multilayered systems built on cheaper, bulk Si platforms.…”
Section: Laser‐processed Planar Photonic Devicesmentioning
confidence: 99%
“…[ 118 ] Moreover, it has recently been demonstrated that a silica cap is necessary to be able to obtain grain‐boundary‐free lateral crystallization of a‐Si thin films on glass substrates, using a fast CW laser scan. [ 119 ] Therefore, laser thermal processing of patterned and glass‐encapsulated Si waveguides could result in low optical losses similar to those achieved in SOI platforms and in the Si core glass‐clad fibers, but with the prospect of allowing for photonic integration within multilayered systems built on cheaper, bulk Si platforms.…”
Section: Laser‐processed Planar Photonic Devicesmentioning
confidence: 99%
“…Laser processing of materials is suitable to modify the crystal structure to achieve a higher degree of crystallinity. Amorphous silicon films and optical fibers were crystallized by long-pulsed 10 or continuous wave 11,12 laser. Adopting this method to MoS 2 , the crystallinity of amorphous magnetron sputtered MoS 2 films on polymer was increased.…”
Section: Introductionmentioning
confidence: 99%
“…Laser processing of materials can modify the crystal structure to achieve a higher degree of crystallinity. Amorphous silicon films and optical fibers were crystallized by long-pulsed [13] or continuous wave (cw) [14,15] laser. Adopting this method to MoS 2 , the crystallinity of amorphous magnetron sputtered MoS 2 films on polymer was increased.…”
Section: Introductionmentioning
confidence: 99%